2003
DOI: 10.1016/s0967-0645(02)00611-2
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemistry of the Bay of Bengal: physical, chemical and primary productivity characteristics of the central and western Bay of Bengal during summer monsoon 2001

Abstract: Reliable data on biological characteristics from the Bay of Bengal are elusive. In this paper, we present results on physics, chemistry and biology simultaneously measured

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
141
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(163 citation statements)
references
References 21 publications
(14 reference statements)
10
141
1
1
Order By: Relevance
“…In an earlier study Murty et al (2000) reported the depth of the SCM in the open-sea region of the Bay of Bengal between 50 and 100 m based on May-June 1996 measurements. However, their chlorophyll a concentrations were extremely low compared to earlier measurements (Radhakrishna et al, 1982, Devassy et al, 1983Sarma and Kumar, 1991;Prasanna Kumar et al, 2002;Madhupratap et al, 2003), especially in the SCM, where they were ~0.1 mg/m 3 .…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…In an earlier study Murty et al (2000) reported the depth of the SCM in the open-sea region of the Bay of Bengal between 50 and 100 m based on May-June 1996 measurements. However, their chlorophyll a concentrations were extremely low compared to earlier measurements (Radhakrishna et al, 1982, Devassy et al, 1983Sarma and Kumar, 1991;Prasanna Kumar et al, 2002;Madhupratap et al, 2003), especially in the SCM, where they were ~0.1 mg/m 3 .…”
Section: Discussioncontrasting
confidence: 56%
“…However, recent measurements using clean techniques (Madhupratap et al, 2003) corroborate the traditional concept that the Bay of Bengal is a region of lesser biological productivity. The reason for this is variously attributed to cloud cover, large sediment load, narrow shelf, stratification, etc (see Qasim, 1977;Sengupta et al, 1977;Radhakrishna, 1978;Gomes et al, 2000).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…In the northern Indian Ocean, primary production in the bright upper ocean is mainly limited by the availability of DIN (Prasarmakumar et al, 2002;Madhupratap et al, 2003). Since the contribution of DIN by atmospheric deposition is relatively less in the northern Indian Ocean (Srinivas et al, 2011;Singh et al" 2012), the riverine DIN input to this area is important for primary production.…”
Section: Nitrogen In Coastal/marine Habitats and Food Websmentioning
confidence: 99%
“…There are numerous studies describing the physical, chemical and biological characteristics of the Bay of Bengal (Kumar et al 2002;Madhupratap et al 2003;Kumar et al 2004). In contrast, only a few studies have focused their attention on the characterization of organic matter with particular reference to the bulk parameters such as organic carbon, nitrogen, carbohydrates and proteins in the Bay (Nandakumar et al 1987;Bhosle and Dhople 1988;Bhosle et al 1992;Unger et al 2005).…”
Section: Introductionmentioning
confidence: 99%